2017
DOI: 10.1155/2017/4297025
|View full text |Cite
|
Sign up to set email alerts
|

Diet-Induced Obesity Is Associated with an Impaired NK Cell Function and an Increased Colon Cancer Incidence

Abstract: Obesity is associated with an increased colon cancer incidence, but underlying mechanisms remained unclear. Previous studies showed altered Natural killer (NK) cell functions in obese individuals. Therefore, we studied the impact of an impaired NK cell functionality on the increased colon cancer risk in obesity. In vitro investigations demonstrated a decreased IFN-γ secretion and cytotoxicity of human NK cells against colon tumor cells after NK cell preincubation with the adipokine leptin. In addition, leptin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
68
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(78 citation statements)
references
References 60 publications
6
68
1
3
Order By: Relevance
“…Interestingly, our own studies demonstrated a leptininduced reduction of IFN-γ secretion in primary human NK cells but not in NK-92 cells. In addition, the data point toward a decreased basal lytic activity against target cells in NK-92 cells compared to primary NK cells (93). Although NK cell lines, like NK-92, are well-established human models for investigations on NK cell functionality and exhibit phenotypical and functional characteristics of primary NK cells, these data underline the limited transferability of findings obtained using immortalized cell lines to conclude the mode of action of primary NK cells (93,95,96).…”
Section: Studies On Leptinmentioning
confidence: 88%
See 4 more Smart Citations
“…Interestingly, our own studies demonstrated a leptininduced reduction of IFN-γ secretion in primary human NK cells but not in NK-92 cells. In addition, the data point toward a decreased basal lytic activity against target cells in NK-92 cells compared to primary NK cells (93). Although NK cell lines, like NK-92, are well-established human models for investigations on NK cell functionality and exhibit phenotypical and functional characteristics of primary NK cells, these data underline the limited transferability of findings obtained using immortalized cell lines to conclude the mode of action of primary NK cells (93,95,96).…”
Section: Studies On Leptinmentioning
confidence: 88%
“…In addition, the data point toward a decreased basal lytic activity against target cells in NK-92 cells compared to primary NK cells (93). Although NK cell lines, like NK-92, are well-established human models for investigations on NK cell functionality and exhibit phenotypical and functional characteristics of primary NK cells, these data underline the limited transferability of findings obtained using immortalized cell lines to conclude the mode of action of primary NK cells (93,95,96). Furthermore, results showed that the leptin effects on NK cells are more pronounced using higher leptin concentrations for incubation experiments (67,93).…”
Section: Studies On Leptinmentioning
confidence: 90%
See 3 more Smart Citations